Choroid plexus dysfunction impairs beta-amyloid clearance in a triple transgenic mouse model of Alzheimer’s disease - González-Marrero, Ibrahim; Giménez-Llort, Lydia; Johanson, Conrad E.; Carmona-Calero, Emilia María; Castañeyra-Ruiz, Leandro; Brito-Armas, José Miguel; Castañeyra-Perdomo, Agustín; Castro-Fuentes, Rafael (Frontiers in Cellular Neuroscience, 2015)
Compromised secretory function of choroid plexus (CP) and defective cerebrospinal fluid (CSF) production, along with accumulation of beta-amyloid (Aβ) peptides at the blood-CSF barrier (BCSFB), likely contribute to complications of Alzheimer’s disease (AD). The AD triple transgenic mouse model (3xTg-AD) at 16 month-old mimics several critical hallmarks of the human disease. In brain, the 3xTg-AD progressively develops β-amyloid (Aβ) plaques and neurofibrillary tangles with a temporal- and regional- specific profile resembling their development in human AD. Currently, little is known about transport and metabolic responses by CP to the disrupted homeostasis of CNS Aβ in AD. This study analyzed the effects of highly-expressed AD-linked human transgenes (APP, PS1 and tau) on lateral ventricle CP function. Confocal imaging and immunohistochemistry revealed an increase in Aβ42 (but not Aβ40) in epithelial cytosol and in stroma surrounding choroidal capillaries; the buildup in insoluble Aβ42 may reflect insufficient clearance transport from CSF to blood. Still, there was increased expression, presumably compensatory, of the choroidal Aβ transporters: the low density lipoprotein receptor-related protein 1 (LRP1) and the receptor for advanced glycation end product (RAGE). A thickening of the epithelial basal membrane and greater collagen IV deposition occurred around capillaries in CP of 3xTg-AD mice, probably curtailing solute exchanges. Moreover, there was attenuated expression of epithelial aquaporin-1 and transthyretin protein compared to non-Tg controls. Collectively these findings indicate CP dysfunction (hypothetically linked to increasing Aβ burden) resulting in less efficient ion transport, concurrently with reduced production of cerebrospinal fluid (less sink action on brain Aβ) and diminished secretion of transthyretin (less neuroprotection against cortical Aβ toxicity). The putative effects of a disabled CP-CSF system on CNS f